Patient-centeredness and empathy in a bilingual interprofessional primary care teaching clinic: a pilot study - Mayer, Sallie D (J Multidiscip Healthc, 2016)
Utilizing the Consultation and Relational Empathy survey, this project examined the perceptions of care team empathy and patient-centeredness between English- and Spanish-speaking patients. From fall through spring semesters, patient surveys from a primary care, interprofessional student-led teaching clinic were collected and analyzed. Overall, mean scores for both English- and Spanish-speaking patients were above the reported normative average for general practitioners. While, overall, patients expressed satisfaction with the student-led teaching clinic in terms of empathy and patient-centeredness, English-speaking patients had higher median scores than Spanish-speaking patients. Analyzed individually, questions related to communication and provider attitudes were scored lower by Spanish-speaking patients. These results demonstrate that student-led clinics can deliver patient-centered care and highlight the continuing need to investigate and address disparities between English- and Spanish-speaking patients with regard to feelings of empathy and patient-centeredness.